EFEK PENYEMBUHAN LUKA BAKAR GEL KOMBINASI EKSTRAK ETANOL DAUN AFRIKA (Vernonia Amygdalina) DAN EKSTRAKETANOLDAUNBANGUN–BANGUN(ColeusamboinicusLour) - Nina Irmayanti Harahap (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
african leaves ( Vernonia Amygdalina )and wake-up leaves (Coleus amboinicus Lour)are plants traditional plants that are used as medicine. Leaves african which is contain flavonoid, saponin, tanin and leaves wake up which is contain flavonoid, tanin, saponin and steroid. This study to find aims out as effect healing of burns.Method : Sample in this study was african leaves and wake-up leaves which were taken purposively without comparing sampel from other regions, then extrated by maceration using ethanol 96 %. Result : Testing of rhe healing effects of burns can be divided in five treatment, positive group using biolacenton , negatif group using basis gel and the last group using the extract ethanol gel EEDA and EEDB concentrations of 4%+2,5%,8%+5%,16%+10%. Given burns to the back of rabbits length with of 2cm, and the gel is applied twice a day for 11 day and diameter measured of the wound. Conclusion : The combination of EEDA and EEDA the ethanol extract the concentration of 16% + 10% was the effective control for healing burns. When compared bioplacenton gel as a healing wound in rabbit.